A comparison of untagged gamma-ray and tagged-neutron yields from 241AmBe and 238PuBe sources. (September 2017) - Scherzinger, J.; Al Jebali, R.; Annand, J.R.M.; Fissum, K.G.; Hall-Wilton, R.; Koufigar, S.; Mauritzson, N.; Messi, F.; Perrey, H.; Rofors, E.
Abstract: Untagged gamma-ray and tagged-neutron yields from 241 AmBe and 238 PuBe mixed-field sources have been measured. Gamma-ray spectroscopy measurements from 1 to 5 MeV were performed in an open environment using a CeBr3 detector and the same experimental conditions for both sources. The shapes of the distributions are very similar and agree well with previous data. Tagged-neutron measurements from 2 to 6 MeV were performed in a shielded environment using a NE-213 liquid-scintillator detector for the neutrons and a YAP(Ce) detector to tag the 4.44 MeV gamma-rays associated with the de-excitation of the first-excited state of 12 C. Again, the same experimental conditions were used for both sources. The shapes of these distributions are also very similar and agree well with previous data, each other, and the ISO recommendation. Our 238 PuBe source provides approximately 2.6 times more 4.44 MeV gamma-rays and 2.4 times more neutrons over the tagged-neutron energy range, the latter in reasonable agreement with the original full-spectrum source-calibration measurements performed at the time of their acquisition. Abstract : Highlights: Untagged gamma-ray (1–5 MeV) and tagged-neutron (2–6 MeV) yields from Be compound sources are measured. Shapes of gamma-ray distributions are similar and agree well with previous data and each other. Shapes of neutron distributions are similar and agree well with previous data, each other, and the ISO 8529-2 recommendation.